Generalized Order and Best Approximation of Entire Function in 𝐿𝑝-Norm - Mohammed Harfaoui (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is the characterization of the generalized growth of entire functions of several complex variables by means of the best polynomial approximation and interpolation on a compact 𝐾 with respect to the set Ω𝑟={𝑧∈𝐂𝑛;exp𝑉𝐾(𝑧)≤𝑟}, where 𝑉𝐾=sup{(1/𝑑)ln|𝑃𝑑|,𝑃𝑑polynomialofdegree≤𝑑,‖𝑃𝑑‖𝐾≤1} is the Siciak extremal function of a 𝐿-regular compact 𝐾.